Reconstruction of the Posterior Cruciate Ligament and Medial Collateral Ligament With a Single Combined Femoral Tunnel - Andre Giardino Moreira da Silva MD; Riccardo Gomes Gobbi MD, PhD; Marcelo Batista Bonadio MD, PhD; Fabio Janson Angelini MD, PhD; José Ricardo Pécora MD, PhD; Camilo Partezani Helito MD, PhD (Video Journal of Sports Medicine)
Background: Lesions of the medial collateral ligament (MCL) are the most common knee ligament injuries and, when they occur in isolation, they often progress with satisfactory outcomes using conservative treatment. However, MCL lesions associated with anterior cruciate ligament or posterior cruciate ligament (PCL) injuries in knee dislocations should be reconstructed to prevent failure of the central pivot. In knees with combined injuries involving the PCL and the MCL, the confluence of tunnels in the medial femoral condyle can be a potential problem during reconstruction surgery. Indications: The indication of this technique is the combined injury of the PCL and the MCL. Technique Description: The technique consists in the reconstruction of the PCL and the MCL with an Achilles tendon allograft. The bone plug of the graft is fixed on the tibial bed with the inlay technique. The graft passes through a single femoral tunnel drilled in the medial femoral condyle, with entrance point on the footprint of the PCL on the inner wall of the condyle and exit on the origin of the native MCL, near to the medial epicondyle. The graft is fixed in the femoral tunnel with an interference screw and continues to the isometric point of the anatomic insertion of the MCL in the tibia, where an interference screw is used to fix it. Results: Results from our group using this technique have shown good clinical outcomes, with complications and failure rates similar to other series in the literature. Discussion/Conclusion: This technique is an excellent option for surgeons, when an Achilles tendon allograft is available, to avoid confluence of tunnels in the medial femoral condyle. It presents good results and acceptable complication rates, compatible with the severity of this lesion. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.